INFLUENCE OF SOCIO-DEMOGRAPHIC FACTORS ON WOMEN ENTREPRENEURS’ PERFORMANCE IN THE SERVICE INDUSTRY – NAMAKKAL REGION - P. Thenmozhi; C. Sankar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The success of female entrepreneurs is an extremely important factor in the development of the regional economy, particularly in terms of developing industries such as the service industry. The purpose of this study is to investigate the impact that socio-demographic parameters, including age, education, marital status, family support, entrepreneurial experience, and financial backing, have on the performance of female entrepreneurs who are engaged in the service industry in the Namakkal region. Data were obtained from 129 female entrepreneurs through the use of a standardized questionnaire. The data were then analyzed using a variety of methods, including percentage analysis, exploratory factor analysis (EFA), reliability testing (Cronbach’s Alpha), and regression analysis. Based on the findings, it is evident that the presence of family and social support, past experience in the field of entrepreneurship, and financial backing all play a significant role in predicting entrepreneurial achievement. The findings highlight the importance of recognizing the relevance of socio-cultural support systems while also highlighting the necessity for specific support programs and policy reforms that improve women’s access to resources and training. For policymakers, educators, and development organizations that are working toward the goal of fostering sustainable women-led entrepreneurship in regional service economies, the study provides critical insights that can be utilized.